2021
DOI: 10.1093/braincomms/fcab019
|View full text |Cite
|
Sign up to set email alerts
|

Subconcussive brain vital signs changes predict head-impact exposure in ice hockey players

Abstract: The brain vital signs framework is a portable, objective, neurophysiological evaluation of brain function at point-of-care. We investigated brain vital signs at pre- and post-season for age 14 or under (Bantam) and age 16–20 (Junior-A) male ice hockey players to (i) further investigate previously published brain vital sign results showing subconcussive cognitive deficits and (ii) validate these findings through comparison with head-impact data obtained from instrumented accelerometers. With a longitudinal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
(24 reference statements)
2
22
0
Order By: Relevance
“…and the fact that participants were engaging in contact sport training between the scans. While short term effects have yet to be examined, longer term participation in contact sports has shown to significantly impact brain vital signs in proportion to the number of head impacts received over a specific period ( Fickling et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…and the fact that participants were engaging in contact sport training between the scans. While short term effects have yet to be examined, longer term participation in contact sports has shown to significantly impact brain vital signs in proportion to the number of head impacts received over a specific period ( Fickling et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the relationship to higher-level cognitive processing, the N400 is an increasingly important brain vital sign response. Clinical ERP studies have repeatedly demonstrated the critical role of the N400 in acquired brain injury ( D’Arcy et al, 2003 ; Gawryluk et al, 2010 ) and recently shown the specific importance in understanding subconcussive/subclinical impairment ( Fickling et al, 2019b , 2021 ). The current N400 effects replicated prior empirical characterization of habituation effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations